Exchange coupled CoPt/FePtC media for heat assisted magnetic recording - Dutta, Tanmay (2019)
L10 FePtC granular media are being studied as potential future magnetic recording media and are set to be used in conjunction with heat assisted magnetic recording (HAMR) to enable recording at write fields within the range of current day recording heads. Media structures based on a FePtC storage layer and a capping layer can alleviate the switching field distribution (SFD) requirements of HAMR and reduce the noise originating from the writing process. However, the current designs suffer from SFD issues due to high temperature writing. To overcome this problem, we study a CoPt/FePtC exchange coupled composite structure, where FePtC serves as the storage layer and CoPt (with higher Curie temperature, Tc) as the capping layer. CoPt remains ferromagnetic at near Tc of FePtC. Consequently, the counter exchange energy from CoPt would reduce the noise resulting from the adjacent grain interactions during the writing process. CoPt/FePtC bilayer samples with different thicknesses of CoPt were investigated. Our studies found that CoPt forms a continuous layer at a thickness of 6 nm and leads to considerable reduction in the saturation field and its distribution.